Competitiveness in manufacturing: a comparison of Germany, Japan and the United States - PILAT, D.; VAN ARK, B. (PSL Quarterly Review, 2013)
A comparative analysis of manufacturing in Germany, Japan and the United States is provided using measures related to levels of relative prices, comparative productivity and unit labour costs. JEL Codes: E00